Physicians' social skills: conceptualization, taxonomy, and behavioral assessment - Breil, Simon Mats; Amelung, Dorothee; Oberst, Sebastian; Rollinger, Torsten; Ahrens, Helmut; Garbe, Amelie; Kadmon, Martina; Marschall, Bernhard; Back, Mitja; Peters, Harm (Perspectives on medical education, 2024)
Social skills (e.g., assertiveness, empathy, ability to accept criticism) are essential for the medical profession and therefore also for the selection and development of medical students. However, the term “social skills” is understood differently in different contexts. There is no agreed upon taxonomy for classifying physicians’ social skills, and skills with the same meaning often have different names. This conceptual ambiguity presents a hurdle to cross-context communication and to the development of methods to assess social skills. Drawing from behavioral psychology, we aim to contribute to a better understanding of social skills in the medical context. To this end, we introduce a theoretically and empirically informed taxonomy that can be used to integrate the large number of different social skills. We consider how skills manifest at the behavioral level to ensure that we focus only on skills that are actually observable, distinguishable, and measurable. Here, behavioral research has shown that three overarching skill dimensions can be seen in interpersonal situations and are clearly distinguishable from each other: agency skill (i.e., getting ahead in social situations), communion skill (i.e., getting along in social situations), and interpersonal resilience (i.e., staying calm in social situations). We show that almost all social skills relevant for physicians fit into this structure. The approach presented allows redundant descriptions to be combined under three clearly distinguishable and behavior-based dimensions of social skills. This approach has implications for the assessment of social skills in both the selection and development of students.